Monitoring of Electrodermal Activity in the Diagnosis of Stress in Stroke Patients (3 Clinical Case Reports) - Anna A. Kuzyukova; Anastasia Yu. Zagaynova; Olga I. Odarushenko; Yana G. Pekhova; Margarita B. Nuvakhova; Larisa A. Marchenkova; Olga O. Borisevich (Вестник восстановительной медицины)
BACKGROUND. Common consequences of stroke are disabling neurological deficits, pain, cognitive and affective disorders that cause distress in patients, but generally accepted diagnostic methods are not always successful in detecting it. Currently, there is an increasing accumulation of data that the assessment of the level of sympathetic activation according to the parameters of electrodermalic activity (EDA) is effective for the diagnosis of stressful conditions.